2023
DOI: 10.1038/s41565-023-01377-4
|View full text |Cite
|
Sign up to set email alerts
|

DNA storage in thermoresponsive microcapsules for repeated random multiplexed data access

Abstract: DNA has emerged as an attractive medium for archival data storage due to its durability and high information density. Scalable parallel random access to information is a desirable property of any storage system. For DNA-based storage systems, however, this still needs to be robustly established. Here we report on a thermoconfined polymerase chain reaction, which enables multiplexed, repeated random access to compartmentalized DNA files. The strategy is based on localizing biotin-functionalized oligonucleotides… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 60 publications
0
13
0
Order By: Relevance
“…Due to the fact that nucleic acid SDRs are the key processes of dynamic DNA nanotechnology, the possibility to achieve temporally programmed pulse outputs could find different applications. For example, being able to intermittently activate DNA-based signaling with specific temporal features could be used to improve multiplexing in DNA-based imaging systems (such as DNA paint) or to temporally control inputs/outputs in DNA-encoded systems with possible applications in DNA computing and drug-delivery. Finally, inspired by the temporal program of gene expression, our strategy can be used to control over time the pulse activation of synthetic genes for different synthetic biology applications, including diagnostic, therapeutic, and biofuel production. , …”
Section: Discussionmentioning
confidence: 99%
“…Due to the fact that nucleic acid SDRs are the key processes of dynamic DNA nanotechnology, the possibility to achieve temporally programmed pulse outputs could find different applications. For example, being able to intermittently activate DNA-based signaling with specific temporal features could be used to improve multiplexing in DNA-based imaging systems (such as DNA paint) or to temporally control inputs/outputs in DNA-encoded systems with possible applications in DNA computing and drug-delivery. Finally, inspired by the temporal program of gene expression, our strategy can be used to control over time the pulse activation of synthetic genes for different synthetic biology applications, including diagnostic, therapeutic, and biofuel production. , …”
Section: Discussionmentioning
confidence: 99%
“…Adapted with permission. [ 45 ] Copyright 2023, Springer Nature. D) Content‐addressable DNA data storage system.…”
Section: In Vitro Dna Data Storagementioning
confidence: 99%
“…For example, Bögels et al. recently demonstrated that storing DNA data in thermoresponsive microcapsules enables multiplexed and repeated random data access [ 45 ] (Figure 5C). They achieved this by enhancing the fidelity of PCR amplification through constraining the reaction into microreactors.…”
Section: In Vitro Dna Data Storagementioning
confidence: 99%
See 2 more Smart Citations